Unraveling synergistic mechanisms of polyacrylamide coagulation and Fe2+/CaO2 Fenton-like oxidation to enhance sludge dewatering - He, Dongqin; Zhu, Tingting; Sun, Mingkai; Chen, Jingyi; Luo, Hongwei; Li, Jun (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
[Display omitted] •Fe2+/CaO2 system can enhance sludge dewatering effectively.•Fe2+ promotes the decomposition of in-situ produced H2O2 to breakdown TB-EPS.•Pre-addition of PAM before Fe2+/CaO2 treatment can achieve better sludge dewatering performance.•The dewatering mechanism of PAM/Fe2+/CaO2 treatment was elucidated. Enhancing sludge dewatering can effectively reduce the operational costs of wastewater treatment plants. In the present study, a synergistic process combining polyacrylamide (PAM) coagulation with Fe2+/CaO2 Fenton-like oxidation was proposed to improve the performance of sludge dewatering. The findings indicate that pre-addition of PAM before Fe2+/CaO2 treatment yielded superior dewatering performance, reducing the water content from 78.6% to 73.1% and the capillary suction time (CST) from 32.9 s to 19.5 s, respectively. Even with a CaO2 dosage of 62.5 mg/g DS, the ultimate pH of the filtrate remained near neutral, and effective dewatering performance was consistently attained. Results of particle size and zeta potential revealed that the addition of PAM enhanced the particle size by electric neutralization and bridging, thus accelerating sludge filtration. Furthermore, Fe2+/CaO2 facilitated the conversion of hydrophilic organic matter in tightly bound EPS (TB-EPS) to soluble EPS (SB-EPS) and loosely bound EPS (LB-EPS), and lysis of the sludge cells, contributing to a decrease in water content. Molecular analysis of EPS through Fourier-transform infrared spectroscopy (FT-IR) further elucidated the breakdown of hydrophilic functional groups by this combined method. Additionally, the changes of Fe2+, Fe3+, and H2O2 concentrations were investigated to explore the mechanism of enhanced sludge dewatering from a kinetic perspective. Ultimately, the concentration of typical heavy metals in the treated sludge sample significantly decreased, leading to a reduction in environmental risks. Overall, this study employed the safe and stable CaO2 as the source of H2O2, combined with Fe2+ to form a Fenton-like system. Meanwhile, PAM was utilized to flocculate the sludge firstly, and then Fe2+/CaO2 oxidation system was carried out to enhance sludge dewatering, which provided a promising sludge dewatering approach with potential applications.